Probiotics in Ankylosing Spondylitis: A Possible Potency - Sumartini Dewi; Stefanie Yuliana Usman; Guntur Darmawan; Dolvy Girawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Ankylosing Spondylitis (AS) is a common autoimmune arthritis which prevalence ranging from 0.1% up to 1.4% globally. Furthermore, in Asian population the prevalence of AS was increasing overtime. Up until now, there were several treatment options available in treating AS in Indonesia. However, there was still some limitations in complete remission achievement and some have limitation in potential adverse drug reaction. Eventually, these affect both patients’s daily activity and their quality of life.There were studies demonstrated the association between intestinal dysbiosis and inflammatory rheumatic disorders. Previous studies also presented there was an altered composition of gut microbiota in AS patients. Probiotic in the other hand, has been known previously for its efficacy in treating intestinal dysbiosis. Hence, this review aimed to identify potencies, efficacy and safety of probiotics as AS treatment options.